2011
DOI: 10.3389/fnhum.2011.00134
|View full text |Cite
|
Sign up to set email alerts
|

Human Cortical Activity Evoked by the Assignment of Authenticity when Viewing Works of Art

Abstract: The expertise of others is a major social influence on our everyday decisions and actions. Many viewers of art, whether expert or naïve, are convinced that the full esthetic appreciation of an artwork depends upon the assurance that the work is genuine rather than fake. Rembrandt portraits provide an interesting image set for testing this idea, as there is a large number of them and recent scholarship has determined that quite a few fakes and copies exist. Use of this image set allowed us to separate the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 36 publications
6
61
0
Order By: Relevance
“…For example, Huang et al (2001) used functional magnetic resonance imaging of the Figure 1 The important arenas over which authenticity operates as far as works of art themselves are concerned. These are the material authenticity of the original and its possible alterations with time, the aesthetic desire for completed works whose value lies in their visual appreciation, and the conceptual, which relates to the increasingly important function of works of art to exist independently of any physical form or fixed materiality, as in ethnographic and post-modern contexts.…”
Section: Authenticity and The Built Heritagementioning
confidence: 99%
“…For example, Huang et al (2001) used functional magnetic resonance imaging of the Figure 1 The important arenas over which authenticity operates as far as works of art themselves are concerned. These are the material authenticity of the original and its possible alterations with time, the aesthetic desire for completed works whose value lies in their visual appreciation, and the conceptual, which relates to the increasingly important function of works of art to exist independently of any physical form or fixed materiality, as in ethnographic and post-modern contexts.…”
Section: Authenticity and The Built Heritagementioning
confidence: 99%
“…Therefore, it seems that LO activity during the viewing of artworks is not strictly related to the extraction of low-level shape/object information: it is also related to the aesthetic appreciation of an image, at least when the image http://dx.doi.org/10.1016/j.bandc.2015.01.008 0278-2626/Ó 2015 Elsevier Inc. All rights reserved. is artistic, and hence more naturally fosters an aesthetic orientation (Huang, Bridge, Kemp, & Parker, 2011;Kirk, Skov, Hulme, Christensen, & Zeki, 2009;Noguchi & Murota, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…By recording the brain activity of 10 male and 10 female participants while they were appreciating examples of artistic and natural visual stimuli, Cela-Conde et al explored possible differences between men and women's neural correlates of aesthetic preference [34]. Using fMRI, Huang et al identified that authenticity of arts had no direct effect on the cortical visual areas responsive to the paintings, but there was a significant psycho-physiological interaction between frontopolar cortex and the lateral occipital area [35]. After a conjunction analysis of brain activity of 21 subjects, Ishizu and Zeki found out that only one cortical area located in the medial orbito-frontal cortex was active during the experience of musical and visual beauty [36].…”
Section: Modeling Esthetics Perception Of Visual Artsmentioning
confidence: 99%